Furious 7 - Ludacris; Statham, Jason; Johnson, Dwayne The Rock; Brewster, Jordana; Rodriguez, Michelle; Russell, Kurt; Walker, Paul; Diesel, Vin ([United States], 2015)
Deckard Shaw is out for revenge against Dominic Toretto and his crew, following the death of his brother in Fast & Furious 6. Before Shaw can do that, Dom plans to take him out first with help from Brian, Ronan, Tej, and Letty.
"Furious 7 offers edge-of-the-seat excitement with outlandish action sequences, inventive stunts, hilarious cartoonish moments and even some touching emotion."--USA Today
"Fast-moving fight scenes, outrageous auto antics and a sprinkling of ridiculous one-liners make Furious 7 a campy, crowd-pleasing escape."--Associated Press
"The hit muscle-car franchise does itself and the late Paul Walker proud with a solid seventh entry."--Variety
Keywords: Crime; Fast cars